Free-Rising Bubbles Bounce More Strongly from Mobile than from Immobile Water–Air Interfaces - Vakarelski, Ivan U. (Langmuir, 2020)
[Image: see text] Recently it was reported that the interface mobility of bubbles and emulsion droplets can have a dramatic effect not only on the characteristic coalescence times but also on the way that bubbles and droplets bounce back after collision (Vakarelski, I. U.; Yang, F.; Tian, Y. S.; Li, E. Q.; Chan D. Y. C.; Thoroddsen, S. T. Sci. Adv.2019, 5, eaaw4292). Experiments with free-rising bubbles in a pure perfluorocarbon liquid showed that collisions involving mobile interfaces result in a stronger series of rebounds before the eventual rapid coalescence. Here we examine this effect for the case of pure water. We compare the bounce of millimeter-sized free-rising bubbles from a pure water–air interface with the bounce from a water–air interface on which a Langmuir monolayer of arachidic acid molecules has been deposited. The Langmuir monolayer surface concentration is kept low enough not to affect the water surface tension but high enough to fully immobilize the interface due to Marangoni stress effects. Bubbles were found to bounce much stronger (up to a factor of 1.8 increase in the rebounding distance) from the clean water interface compared to the water interface with the Langmuir monolayer. These experiments confirm that mobile surfaces enhance bouncing and at the same time demonstrate that the pure water–air interfaces behave as mobile fluid interfaces in our system. A complementary finding in our study is that the ethanol–air interface behaves as a robust mobile liquid interface. The experimental findings are supported by numerical simulations of the bubble bouncing from both mobile and immobile fluid interfaces.